Optimizing Interaction Parameters Of Various Thermodynamics Models using MATLAB To Estimate Activity Coefficients Of Azeotropic Mixtures - Singh, Parminder; Sharma, Puja (International journal of engineering and advanced technology, 2019)
The calculation of the liquid-vapor phase equilibrium conditions in multicomponent mixtures is a subject of general interest for engineering. So in this article, interaction parameters of various thermodynamics models are optimized using MATLAB and the vapor-liquid equilibrium conditions are estimated through the application of the modified Raoult’s equation. Activity coefficients of azeotropic mixtures are also estimated. The application of conventional models is restricted for those systems that exhibit irregular behavior, that is, they form azeotropic. In these cases, the validity of these models is limited since the experimental data is not satisfactorily explained. The UNIFAC model completely explains the experimental data of non-ideal systems quite well.